ADVANTAGES OF NEW TECHNOLOGIES IN EDUCATION - Khalilova Barnogul Abdulazizovna; Khamrakulova Ravshanoy Abdulakhatovna (Modern American Journals, 2025)
The article examines the prospects for implementing innovative technologies in teaching, the modern understanding of innovative technologies, and their role and significance. It considers the challenges of using various teaching methods in problem-based learning, problem-solving, finding solutions to situations, and the prospects of innovative technologies. The effectiveness of informatization and digitalization of the educational process is discussed, which should create a firm conviction that these qualities of organizing the educational process are characteristic of modern society. The article also explores designing learning by the requirements of the time, as well as using and developing logical thinking skills.
Keywords: Informatization effect, sphere of activity, equipment and technologies, level of scientific development, systemic reform, methodological basis, periodic application, spectrum, quality assurance, modernization, digitalization.